BMAA in cycad-feeding Lepidoptera: defensive sequestration or bioaccumulation? - Whitaker, Melissa R. L.; Banack, Sandra Anne; Mescher, Mark C.; Cox, Paul Alan; De Moraes, Consuelo M. (Frontiers in Ecology and Evolution, 2023)
Many herbivorous Lepidoptera accumulate plant toxins within their own tissues as a defensive strategy. Pioneering research in this area was conducted by Miriam Rothschild and Deane Bowers, who showed that the cycad-feeding butterfly Eumaeus atal